2012
DOI: 10.1016/j.semarthrit.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Testing in Patients with Rheumatoid Arthritis and Key Cardiovascular-Related Comorbidities: A Medicare Analysis

Abstract: Objective-For patients with rheumatoid arthritis (RA) and comorbid cardiovascular disease (CVD), diabetes, or hyperlipidemia, annual lipid testing is recommended to reduce morbidity and mortality from comorbidities. Given trends encouraging complex patients to receive care in "medical homes," we examined associations between regularly seeing a primary care provider (PCP) and lipid testing in RA patients with cardiovascular-related comorbidities. Publisher's Disclaimer: This is a PDF file of an unedited manuscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
1
22
2
2
Order By: Relevance
“…In our longitudinal study, examining only incident hypertension cases, 64% of RA patients (compared to 49% without RA) with incident hypertension remained undiagnosed/untreated. Our results highlight that undiagnosed hypertension is a pervasive problem that is compounded for RA patients--suggesting gaps in current clinical care much like our previous work reporting low lipid testing in Medicare patients with RA (5, 6). …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In our longitudinal study, examining only incident hypertension cases, 64% of RA patients (compared to 49% without RA) with incident hypertension remained undiagnosed/untreated. Our results highlight that undiagnosed hypertension is a pervasive problem that is compounded for RA patients--suggesting gaps in current clinical care much like our previous work reporting low lipid testing in Medicare patients with RA (5, 6). …”
Section: Discussionsupporting
confidence: 59%
“…Based upon our prior work demonstrating low lipid testing in Medicare RA patients, (5, 6) we broadly hypothesized that RA patients, despite increased CVD risk, have not received as much CVD preventive care as non-RA peers. Specifically, in the present work we focus on hypertension, a prevalent and modifiable risk factor for increased CVD in both RA patients and the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Toms et al studied a cohort of RA patients without established CVD or diabetes and found that in the high risk group, 2-26% (depending on risk stratification group), had sufficiently high risk to require statin therapy, although the majority of them (58-95%) were not treated (16). Bartels and colleagues studied RA patients enrolled in Medicare who were older than age 65 and had both RA and concomitant CVD (90%), diabetes (46%), or hyperlipidemia (64%) (17). In this high risk cohort with CVD, 30% of the RA patients studied saw a PCP less than once per year and 1 in 3 lacked annual cholesterol screening (17).…”
Section: Traditional CV Risk Factors In Ra: How Should/do We Manage Tmentioning
confidence: 99%
“…Bartels and colleagues studied RA patients enrolled in Medicare who were older than age 65 and had both RA and concomitant CVD (90%), diabetes (46%), or hyperlipidemia (64%) (17). In this high risk cohort with CVD, 30% of the RA patients studied saw a PCP less than once per year and 1 in 3 lacked annual cholesterol screening (17). Finally, Lindhardsen et al reported a marked discrepancy in secondary prevention in RA patients discharged from the hospital after suffering a first myocardial infarction (MI).…”
Section: Traditional CV Risk Factors In Ra: How Should/do We Manage Tmentioning
confidence: 99%
“…The CVD risk imposed by RA is both under-recognised and underassessed in primary care 5 6. Furthermore, a recent study reported that 30% of RA patients with comorbid CVD, diabetes or hyperlipidaemia consult a primary care physician (PCP) less than once a year, despite frequent visits to other providers such as rheumatologists 5…”
Section: Introductionmentioning
confidence: 99%